2006
DOI: 10.1038/sj.onc.1209858
|View full text |Cite
|
Sign up to set email alerts
|

PRIMA-1MET induces nucleolar accumulation of mutant p53 and PML nuclear body-associated proteins

Abstract: We have previously identified PRIMA-1, a low molecular weight compound that restores the transcriptional transactivation function to mutant p53 and induction of apoptosis. To explore the molecular mechanism for PRIMA-1-induced mutant p53-dependent apoptosis, we examined the intracellular distribution of mutant p53 upon treatment with PRIMA-1 MET by immunofluorescence staining. We found that PRIMA-1 MET induced nucleolar translocation of mutant p53 and the promyelocytic leukemia (PML) nuclear body-associated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 49 publications
0
33
1
Order By: Relevance
“…We have previously observed that PRIMA-1 and PRIMA-1 MET can induce redistribution of mutant p53 from the nucleoplasm to nucleoli, and that the PML-NB-associated proteins PML, CBP and Hsp70 also accumulate in nucleoli (Ro¨kaeus et al, 2007). PML is a transcription target of p53 and PML overexpression was shown to recruit p53 into PML-NBs and stabilize p53 (Fogal et al, 2000;de Stanchina et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously observed that PRIMA-1 and PRIMA-1 MET can induce redistribution of mutant p53 from the nucleoplasm to nucleoli, and that the PML-NB-associated proteins PML, CBP and Hsp70 also accumulate in nucleoli (Ro¨kaeus et al, 2007). PML is a transcription target of p53 and PML overexpression was shown to recruit p53 into PML-NBs and stabilize p53 (Fogal et al, 2000;de Stanchina et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…We previously found that PRIMA-1 MET treatment causes a nucleolar accumulation of mutant p53, along with PML, CBP and Hsp70 (Ro¨kaeus et al, 2007).…”
Section: Prima-1 Met Causes Redistribution Of Mutant P63mentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, PRIMA-1 induces expression of heat-shock protein 90 (Hsp90) and enhances its binding to mutant p53, suggesting that Hsp90 mediates mutant p53 refolding (Rehman et al, 2005). Moreover, PRIMA-1MET triggers redistribution of mutant p53 to nucleoli, along with three other promyelocytic leukemia protein (PML) body-associated proteins, PML, cAMPresponsive binding protein (CBP) and heat-shock protein 70 (Hsp70) (Ro¨kaeus et al, 2006). PRIMADead, an inactive structural analog, failed to induce nucleolar redistribution of mutant p53 and other PML body-associated proteins, consistent with the notion that nucleolar translocation and perhaps interaction with Hsp70 and other PML body proteins plays a role in reactivation of mutant p53.…”
Section: Small Molecules That Target Mutant P53mentioning
confidence: 99%
“…earlier study showed that PRIMA-1 MET increases the level of HSP70, a chaperone involved in protein folding (Rokaeus et al, 2007), suggesting an increase in the unfolded protein fraction on PRIMA-1 MET treatment. Interestingly, XBP1 contains a putative p53 response element, consistent with the involvement of p53 in ER stress (Ceribelli et al, 2006) and the upregulation of XBP1 by PRIMA-1 MET in this study.…”
Section: Prima-1 Induces Er Stress-mediated Apoptosis Jmr Lambert Et Almentioning
confidence: 99%